INITIATING RELIGIOUS MODERATION EDUCATION IN THE ERA OF MANUSCRIPT-BASED EDUCATION 4.0: HERMENEUTIC ANALYSIS OF SERAT WEDHARAGA - Khotijah Khotijah; Dedi Wahyudi; Nawang Wulandari; Faisal Mahmoud Adam Ibrahim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
Education must continue to adapt to changes to educate the younger generation for the dynamics of industrial revolution 4.0. Religious moderation is practiced in a variety of ways, most notably in education. Reintroducing the Indonesian nation's old writings is one technique to impart religious moderation instruction to the younger generation. With the richness of cultural works that Indonesia has such as ancient manuscripts, it should be able to lead people to live in harmony and peace. However, as a result of the growth of the industrial revolution 4.0, what is happening in our Indonesian life nowadays reveals that many deeds lead to violence and criminality in the name of religion. This study aims to investigate the concept of religious moderation education in the era of manuscript-based education 4.0, which is done using Serat Wedharaga's hermeneutic analysis approach. Researchers will use all available data and analysis to demonstrate how Serat Wedharaga, the work of Raden Ngabehi Ranggawarsita, presents a concept linked to moderation education, which is critical in today's society in the education 4.0 era. This research is based on qualitative data. The data sources in this study consist of two kinds of data, namely primary data sources in the form of Serat Wedharaga manuscript, and secondary data in the form of books, photos, documents, journals, and previous research results that are relevant or related to primary data and research themes. After conducting an in-depth study, it is found that Serat Wedharaga incorporates educational principles such as andragogy education and the value of self-regulation, which includes honesty, tepasalira (tolerance), awas lan eling (cautiousness), and rejecting rumor. The educational values in Serat Wedharaga are relevant to the concept of religious moderation in the education 4.0 era.